Non-Performing Loans and Economic Growth in Nigeria: A Dynamic Analysis - Akinola Morakinyo; Mabutho Sibanda (SPOUDAI - Journal of Economics and Business, 2016)
In this paper, utilising the endogenous growth model, we assess the joint long-run determination of economic growth by non-performing loans (NPLs) and by other factors that include bank credit to the economy, gross secondary school enrolment, government expenditure growth rate and the inflation rate in Nigeria using the bank-based approach. The quarterly data sample is between 1998 and 2014. We incorporate the NPLs level in a multivariate model using the ARDL procedure. The results from the bound test suggest the existence of long-run co-movement of these variables and economic growth. All variables in the model are statistically significant in the long run. The NPLs level and bank credit to the economy were found to have a negative and a direct impact on economic growth respectively. On the whole, financial pollution (NPLs) and positive financial utility (from bank credit to the economy) show a remarkable impact of financial development on economic growth in Nigeria. The error correction mechanism shows a very slow restoration to equilibrium in the next period once the system is distorted. The study recommends a higher level of proactive policies both to curb the growth of NPLs and to drive credit by banks to the economy's private sector.
Keywords: E51; G21; O47; 330; Cointegration; non-performing loans; financial depth; economic growth; ARDL